Effect of Temperature and Baking Time on the Quality of Sponge Cake - Desla, Afifah Tiara; Elida, Elida (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
This study aims to analyze the effect of temperature and baking time (temperature 160ᴼ C and time 30 minutes, temperature 170ᴼ C and time 25 minutes, temperature 180ᴼ C and time 20 minutes) on the quality of sponge cake including the quality of volume, shape, color, aroma, texture. and taste. This type of research is a pure experiment using the Completely Randomized Design (CRD) method which has been carried out 3 treatments and 3 repetitions. The object of this research is sponge cake with a temperature and time difference of 160ᴼ C for 30 minutes, 170ᴼ C for 25 minutes and a temperature of 180ᴼ C for 20 minutes on the quality of sponge cake. The types and sources of data used were obtained directly from 5 expert panelists by filling out the organoleptic test format on the quality of the sponge cake. Data analysis used Analysis of Variance (ANOVA). If the analysis of variance shows Fcount > Ftable, Duncan's test will be performed. The results showed that the difference in temperature and time had no significant effect on the quality of volume, shape, color, aroma, texture and taste. Based on research conducted that H0 is accepted, Ha is rejected stating that there is no effect of temperature and baking time on the quality of sponge cake (temperature 160ᴼ C and time 30 minutes, temperature 170ᴼ C and time 25 minutes, temperature 180ᴼ C and time 20 minutes). So that the Advanced Test (Duncan) was not carried out.